Characterizing corn-straw-degrading actinomycetes and evaluating application efficiency in straw-returning experiments - Gong, Xiujie; Yu, Yang; Hao, Yubo; Wang, Qiuju; Ma, Juntao; Jiang, Yubo; Lv, Guoyi; Li, Liang; Qian, Chunrong (Frontiers in Microbiology, 2022)
Corn straw is an abundant lignocellulose resource and by-product of agricultural production. With the continuous increase in agricultural development, the output of corn straw is also increasing significantly. However, the inappropriate disposal of straw results in wasting of resources, and also causes a serious ecological crisis. Screening microorganisms with the capacity to degrade straw and understanding their mechanism of action is an efficient approach to solve such problems. For this purpose, our research group isolated three actinomycete strains with efficient lignocellulose degradation ability from soil in the cold region of China: Streptomyces sp. G1T, Streptomyces sp. G2T and Streptomyces sp. G3T. Their microbial properties and taxonomic status were assessed to improve our understanding of these strains. The three strains showed typical characteristics of the genus Streptomyces, and likely represent three different species. Genome functional annotation indicated that most of their genes were related to functions like carbohydrate transport and metabolism. In addition, a similar phenomenon also appeared in the COG and CAZyme analyses, with a large number of genes encoding carbohydrate-related hydrolases, such as cellulase, glycosidase and endoglucanase, which could effectively destroy the structure of lignocellulose in corn straw. This unambiguously demonstrated the potential of the three microorganisms to hydrolyze macromolecular polysaccharides at the molecular level. In addition, in the straw-returning test, the decomposing consortium composed of the three Streptomyces isolates (G123) effectively destroyed the recalcitrant bonds between the various components of straw, and significantly reduced the content of active components in corn straw. Furthermore, microbial diversity analysis indicated that the relative abundance of Proteobacteria, reportedly associated with soil antibiotic resistance and antibiotic degradation, was significantly improved with straw returning at both tested time points. The microbial diversity of each treatment was also dramatically changed by supplementing with G123. Overall, G123 has important biological potential and should be further studied, which will provide new insights and strategies for appropriate treatment of corn straw.